2020
DOI: 10.1088/1757-899x/712/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Porosity of Porous Concrete Pavement Containing Nano Black Rice Husk Ash

Abstract: Rice husk ash (RHA) as replacement material in the conventional concrete mixture has been widely studying around the world. However, there is a lack of study on nanoparticle produced from black rice husk ash (BRHA) used as a replacement material in porous concrete pavement mixture. Therefore, this study aims to evaluate the performance of porous concrete pavement containing nano black rice husk ash in terms of compressive strength, porosity and its correlation. A nano BRHA dosage of 10, 20, 30 and 40% by weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Authors in a study 25 observed improvement in concrete mechanical properties when joint addition of WSA with metakaolin was utilized to replace cement along with nylon fibers. Concrete mechancial strength was improved 26 significantly with 20% substitutions of cement with WSA, similar results were noted by researchers. 27 Fine aggregate like sand could be also 28 replaced with waste materials like waste marble powder (WMP).…”
Section: Introductionsupporting
confidence: 88%
“…Authors in a study 25 observed improvement in concrete mechanical properties when joint addition of WSA with metakaolin was utilized to replace cement along with nylon fibers. Concrete mechancial strength was improved 26 significantly with 20% substitutions of cement with WSA, similar results were noted by researchers. 27 Fine aggregate like sand could be also 28 replaced with waste materials like waste marble powder (WMP).…”
Section: Introductionsupporting
confidence: 88%
“…Compressive strength was conducted after the curing time period of 7 and 28days this test show the strength of material to with stand against the application of load in compression test load is applied to cube until the rapture of cube takes place [9]. The compressive strength goes on decreasing with increasing % of partially replacement of cement with SCBA and RHA.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The compressive strength goes on decreasing with increasing % of partially replacement of cement with SCBA and RHA. The maximum compressive strength was absorbed at 5% replacement at 28days curing and minimum was at 15% because of the porous nature of rice husk there is minimum resistance to applied load [9] or because of the use of a high quantity of agricultural waste put impact on water penetration in concrete which results in production of lesser amount of calcium hydroxide [10]. The results have been plotted in Figure .3.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The important mechanical properties of typical pervious concrete, such as compressive strength, flexural strength, split tensile strength, porosity, permeability, and density or unit weight, are shown in Table 1. According to the literature, the unit weight of pervious concrete in the general field is approximately 1500-2000 kg/m 3 [11][12][13][14][15][16][17][18]. This light density is due to the fact that porous concrete has pores ranging from 15 -35% with a permeability of 4.2 mm/sec.…”
Section: Introductionmentioning
confidence: 99%